Perancangan Prototipe SIHEJO: Aplikasi Penghitung Emisi Karbon di Kota Bandung Menggunakan Metode Design Thinking - Irfan Walhidayah; Agung Ukki Galih Cahyaningsih (JUSIFOR : Jurnal Sistem Informasi dan Informatika, 2026)
Climate change has become a critical global issue that requires increased public awareness and participation in reducing carbon emissions. This study aims to develop a prototype of SIHEJO (Sistem Informasi Hijau), a mobile-based application designed to calculate carbon emissions in a manner contextualized to the urban environment of Bandung City. The research adopts the Design Thinking approach, consisting of five stages: empathize, define, ideate, prototype, and test, to ensure a user-centered solution. SIHEJO integrates key features, including activity-based carbon emission calculation, interactive dashboards, sub-district-level emission mapping, and personalized recommendations for emission reduction. The prototype was evaluated using the System Usability Scale (SUS) involving potential users. The results show an average SUS score of 90.25, categorized as excellent, indicating high usability and user acceptance. This study contributes to the development of locally relevant environmental applications that are not only informative but also educational and interactive, with the potential to support sustainable urban development policies.